Printing 2D Materials - Torrisi,F; Carey,T (2018)
This chapter reviews the state of the art of printed electronics and optoelectronics with graphene and related materials (GRMs). It summarizes the process steps involved in the formulation of GRM inks. The chapter outlines all of the most common printing techniques and offers an overview of the electronic inks formulation techniques and their characterization techniques. It reviews the techniques for the exfoliation of layered crystals and discusses the stabilisation strategies of exfoliated flakes in liquid. The chapter reviews the tuning of the rheology of 2D material inks and discusses the development of printing strategies for graphene and 2D crystal inks and hybrid combinations. It finally discusses the printed electronic and optoelectronic devices with GRMs. The infinite possibilities offered by the printing and solution-processing approach have enabled exploiting the full potential of different conducting, semiconducting, and dielectric 2D-crystals for all inkjet printed heterostructures.